Two Newsrooms and the Daily Reinvention of Journalism - Mesquita, Giovana Borges (Brazilian journalism research, 2018)
This paper is the result of an ethnographic study conducted on one of the most important Spanish newspapers, the La Vanguardia in its digital version, the lavanguardia.com, and on diariodepernambuco.com, the digital version of the oldest circulation newspaper in Latin America, the Diario de Pernambuco, in Recife (PE). This article aims to analyze how the relationship between journalists and what we call the potent audience has caused complex changes to the way journalism is conducted, affecting both the professionals and the news production. It also reflects on new roles taken on by journalists who now perform both journalistic and marketing assignments, which has changed the routine in newsrooms and raised important questions about what the values are that guide journalists in selection processes, news gathering and editing in a post-social media world. O trabalho é fruto de uma pesquisa de cunho etnográfico em um dos mais importantes diários espanhóis, o La Vanguardia em sua versão digital, lavanguardia.com, e no diariodepernambuco.com, versão digital do jornal mais antigo em circulação da América Latina, o Diario de Pernambuco, sediado no Recife (PE). O artigo busca analisar como a relação entre jornalistas e o que denominamos audiência potente tem provocado complexas alterações no mundo do trabalho do jornalismo, afetando o profissional e a produção noticiosa. Também se propõe a refletir sobre novas funções assumidas pelos jornalistas que reúnem atribuições do campo jornalístico e do marketing, mudando a rotina nas redações e levando a questionamentos importantes sobre quais são os valores que norteiam os jornalistas nos processos de seleção, apuração e edição pós redes sociais. El trabajo es fruto de una investigación de cuño etnográfico realizada en uno de los más importantes diarios españoles, el La Vanguardia en su versión digital, el lavanguardia.com, y en el diariodepernambuco.com, versión digital del periódico más antiguo en circulación de América Latina, el Diario de Pernambuco, con sede en Recife (PE). El artículo busca analizar cómo la relación entre periodistas y lo que denominamos Audiencia Potente ha provocado complejas alteraciones en el mundo del trabajo del periodismo, afectando al profesional y la producción noticiosa. También se propone reflexionar sobre nuevas funciones asumidas por los periodistas que reúnen atribuciones del campo periodístico y del marketing, cambiando la rutina en las redacciones y llevando a cuestionamientos importantes sobre cuáles son los valores que orientan a los periodistas en los procesos de selección, recopilación y edición post-redes sociales.